Implementation of the Role of Ankum and Papera in the Process of Resolving Military Cases in the Jurisdiction - Susanto, Arif; Siregar, Taufik; Amal, Ridha Haykal (Borong Newinera Publisher, 2025)
This study aims to analyze the implementation of the role of Ankum (Superiors Who Have the Right to Sentence) and Papera (Case Submission Officers) in the process of resolving military crime cases in the jurisdiction of the Medan High Military Court I. The approach used is qualitative with descriptive-analytical methods through in-depth interviews, document studies, and observations. The focus of the research includes three main aspects, namely the case administration process in the military judicial environment, the application of fast, precise, and simple judicial principles after the integration of the one-stop system under the Supreme Court of the Republic of Indonesia, and the role of the unitary commander in case resolution. The results of the study show that the case administration process still faces obstacles, especially in terms of the completeness of documents and the accuracy of procedures by Ankum and Papera. Although the one-stop system provides an opportunity to speed up the case process, technological limitations and internal resistance are challenges in the application of the principle of fast, precise, and simple justice. In addition, the role of the unit commander as the initial decision-maker greatly affects the smooth process of resolving cases, even though there is a disparity in the understanding of military law among Ankum. This study recommends increasing legal training for Ankum and Papera, stricter supervision of the implementation of legal procedures, and accelerating the digitalization of the military judicial administration system. Thus, these findings make an important contribution to efforts to improve the military justice system to realize efficiency, transparency, and justice.